2014
DOI: 10.1074/mcp.m113.030403
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional Regulation of Human Breast Cancer Cell Proteome by Unliganded Estrogen Receptor β via microRNAs

Abstract: Estrogen receptor ␤ (ER␤) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 79 publications
(95 reference statements)
3
37
0
Order By: Relevance
“…The data obtained from the sequencer were analyzed using iMir, a modular pipeline for comprehensive analysis of small RNA-Seq data, comprising specific tools for adapter trimming, quality filtering, identification of known sncRNAs, novel miRNA prediction, differential expression analysis and target prediction [72, 73]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data obtained from the sequencer were analyzed using iMir, a modular pipeline for comprehensive analysis of small RNA-Seq data, comprising specific tools for adapter trimming, quality filtering, identification of known sncRNAs, novel miRNA prediction, differential expression analysis and target prediction [72, 73]. …”
Section: Methodsmentioning
confidence: 99%
“…Identification of differentially expressed sncRNAs was performed with the Bioconductor DESeq package available in iMir tool [72, 73]. A negative binomial distribution model was used to test differential expression in deep sequencing datasets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2E) [3,73,74]. In BC, unliganded ER␣ has been found able to regulate genes linked to development and differentiation [27] while unliganded ER␤ strongly affects both the genome and the proteome of BC cells by inducing also microRNA expression changes [75,76]. In prostate cancer, the presence of unliganded ER␤ seems to induce apoptosis by a KLF5 tethering mechanism [77].…”
Section: Ligand-independent Signalingmentioning
confidence: 96%
“…A first study reported the effect of unliganded ER␤ expression on BC cell miRNome [109]. Subsequently, Nassa et al [75], considering that ER␤ subtype seems to be the most active in absence of ligand and taking into account its inhibitory role in respect to ER␣ in BC, investigated the activity of unliganded ER␤ in MCF-7 and ZR-75.1 BC cell lines by means of microRNA sequencing (miRNA-Seq). They found 30 miRNAs affected by the presence of unliganded ER␤.…”
Section: Unliganded Ers and Regulation Of Noncoding Rna And Proteomementioning
confidence: 99%